Amantadine in the early treatment of cocaine dependence: a double-blind, placebo-controlled trial - Kampman, Kyle; Volpicelli, Joseph R.; Alterman, Arthur; Cornish, James; Weinrieb, Robert; Epperson, Louise; Sparkman, Thorne; O'Brien, Charles P. (Drug and alcohol dependence, 1996)
A 4-week, double-blind, placebo-controlled trial of amantadine was conducted in 61 cocaine dependent outpatients. Subjects received 100 mg of amantadine 3 times daily. A follow-up visit was conducted at week 8. There were no significant differences between groups in treatment retention, or in the number of benzoylecgonine positive urine samples. Self-reported drug and alcohol use declined in both groups. At week 8 follow-up, self-reported drug use was significantly lower in the placebo group. Amantadine was not effective, and discontinuation of it may have been associated with an increase in cocaine use.